Dampak PPKM Darurat Jawa-Bali Terhadap Pelaku Usaha Coffee Shop Pada Masa Pendemi Covid-19 Di Kecamatan Wonocolo Kota Surabaya - Janah, Miftakhul; Istigfarina, Ulfah; Lamiah, Ni`matul; Faizur Rohman, Moh (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2021)
Abstract: This study aims to determine the impact of the implementation of restrictions on community activities or the Java-Bali emergency PPKM which is an effort from the government to overcome the spread of the covid-19 virus during the current pandemic. The impact of the implementation of this community restriction is very large and is felt by many people, starting from employees, students, and activities that are usually carried out in person/face to face are now carried out online. This impact is also felt by coffee shop business actors in the Wonocolo sub-district, Surabaya. Judging from the reduced sales turnover and the lack of visitors, some of them have to close temporarily, some have to close permanently. This research was conducted with a qualitative descriptive method through the research object of a coffee shop located in the Wonocolo district of Surabaya, the data collection technique used interviews with informants and observations to one of the coffee shops in the Wonocolo district of Surabaya. Keywords: Covid-19 Pandemic, PPKM, Coffee Shop Businesses